Intelligent Jammer on Mobile Network LTE Technology: A Study Case in Bucharest - Capotă, Cristian; Popescu, Mădălin; Bădulă, Eduard-Marian; Halunga, Simona; Fratu, Octavian; Popescu, Mircea (Applied sciences, 2023)
The purpose of this study was to develop a laboratory model that enables the monitoring of communications carried out through mobile phones and their blocking in cases where it is prohibited. The main goal was to realise an intelligent jammer that blocks only illicit communications. The jammer was built with a software-defined radio (SDR) that can be found on the market and is accessible from a financial point of view. This study consisted of an analysis of the behaviour of mobile phones and mobile networks using the long-term evolution (LTE) of UMTS technologies so that the jamming technique can disrupt the communication of the cellular mobile system by using the software-defined radio and Python ecosystem. Because the 5G standalone (5G SA) is not yet implemented in Romania, we could not start developing a laboratory model for jamming this technology. When 5G SA is implemented, we will adapt this intelligent jamming solution to the new technology.